Mubi-Toram lexicon and Afro-Asiatic II: Addenda with *b- - Takács, Gábor (Lingua Posnaniensis, 2023)
The paper is part of a planned longer series designed to step by step reveal the Chadic and wider Afro-Asiatic heritage in the lexical stock of the Mubi-Toram languages which represent the easternmost (26th or 27th)[1] group of the vaste Chadic (i.e., 6th) branch of the gigantic Afro-Asiatic family. [1] Depending on the disputed classification of Mokilko (Mokulu) as either part of the Dangla-Migama group or a separate group itself.